The Impact of Covid-19 Pandemic on Indonesian Consumer and Business Confidence Indicator - salsabiila naedi; Muhammad Iksan (Fakultas Ekonomi & Bisnis Universitas Paramadina, 2021)
Our study has two main aims, which are to utilize the pandemic of coronavirus as a subject of interest. First, this paper purposes of explaining the impact of the coronavirus rate, including the new cases and mortality rate, on consumer sentiment using a proxy of consumer confidence indicators. By the first aim, this paper captures the impact of the pandemic on the consumer side. Second, this paper also aims to explain the impact of coronavirus figures, including the new cases and mortality rate, on the business sentiment using a proxy of business confidence indicators. By the second aim, this paper seizes the impact of the pandemic on the producer side. There is an abundance of international studies that have similar research aims to our study, i.e., Teresine et al. (2021), Chong et al. (2021), Barro et al. (2020), and Baker et al. (2020). Most of these studies emphasize their attention to COVID-19 cases from international cases, i.e., the United States, the Eurozone, and the People's Republic of China. However, a study by Chong and colleagues assessed the impact of the coronavirus on ASEAN countries descriptively. Their studies separately analyzed several Southeast Asian country's economic figures for the first two quarters in 2020. Our result indicates that the impact of COVID-19 on both indicators, consumer and business, is different. This study only finds statistically total death confirmed cases affect business confidence. Our study corroborates with findings from Teresina et al., whose results argue that the spread of pandemics did not affect the consumer confidence index in the Eurozone. Although using different business sentiments, our study finds a similar pattern: business sentiment reacts to increasing total cases confirmed. We suggest our readers have to take our findings with a grain of salt because of the limitation of observations.